Digestibilidade aparente de rações contendo diferentes níveis de fósforo para pacus (Piaractus mesopotamicus) - Lösch, Juliana Alice (2013)
Two experiments were conducted to evaluate the apparent digestibility of diets containing different levels of phosphorus for pacu (Piaractus mesopotamicus). The first experiment aimed to evaluate the apparent digestibility of diets containing different phosphorus levels for pacus, through the decantation method. A total of 60 pacus were used, averaging 151,57±6,43 g in weight, allotted in 6 180-L tanks, with Modified Guelph System, in an experimental design entirely randomized. The fish were fed isonitrogenous, isoenergetic and isocalcium diets, containing 27% of crude protein, 1,50% of calcium and 3000 kcal of DE/kg, with levels of 0,6 and 1,2% of total phosphorus. The fecal samples were taken every 30 minutes in order to decrease the loss of nutrients through leaching. We observed significant differences in treatments. There is a reduction in diets digestibility, with values of 80,06 and 60,55%, decrease in phosphorus apparent digestibility, with values of 86,08 and 72,80% and, consequently, observed a increase residual phosphorus for fish fed with 0,6 and 1,2% of phosphorus, respectively. Therefore, the greater total phosphorus digestibility and consequently lower total phosphorus excretion in feces obtained by the decantation method was observed at diet containing 0,6% of total phosphorus for pacus. The second experiment aimed evaluate the apparent digestibility of rations containing different phosphorus levels for pacus (Piaractus mesopotamicus), through intestinal dissection method. A total of 320 pacus were used, averaging 768,5±36,34 g in weight, allotted in four 5-m3 cages. The fish were fed isonitrogenous, isoenergetic and isocalcium diets, containing 27% of crude protein, 1,50% of calcium and 3000 kcal of DE/kg, with levels of 0,6; 0,8; 1,0 and 1,2% of total phosphorus. The fecal samples were performed by opening the fish side for removal of feces present in the rectum, and the fish sent for analysis of whole body chemical composition. We observed significant differences (P<0,01) between treatments for apparent digestibility coefficient of the diet, apparent digestibility of phosphorus, available phosphorus and residual phosphorus. There is a linear decrease in apparent digestibility of the diet and apparent digestibility of phosphorus with increase phosphorus levels in the diet, the highest values being observed for the diet with 0,6% of total phosphorus, while for available phosphorus and residual phosphorus there was a linear increase with inclusion levels of total phosphorus in the feed. There were no significant differences for wholly body chemical composition of pacu. Therefore, most phosphorus digestibility of the diet, obtained by intestinal dissection method, was observed in diet containing 0,6% of total phosphorus for pacu and the different phosphorus levels had no effect in whole body of pacus